Upaya pencegahan risiko LGBT pada remaja SMA (LGBT risk prevention efforts in Senior High School adolescents) - Esi Afriyanti; Elvi Oktarina; Feri Fernandes (Warta Pengabdian Andalas)
The problem of lesbian, gay, bisexual and transgender, or known as LGBT, has become prominent in the world in more than a decade. This problem is also a concern in Indonesia along with the rise of HIV cases. From 1990 to 2016 there was an increase in HIV and AIDS cases where an increase in HIV AIDS cases was transmitted by heterosexual sexual activity. Heterosexual is mostly done by LGBT people. Most homosexuals (Lesbian, Gay and transgender) begin to realize that they have different tendencies when they are young. Studies show homosexual behavior and same-sex attraction have been encountered since the age of 15. This situation shows that the school age group is the age of the vulnerable to start engaging in same-sex relationships. While the decision to become homosexual or majadi lesbian occurs mostly in young adults or at the age when they are already students. For this reason, early prevention of LGBT is needed. This prevention can be done by early detection of the tendency for sexual behavior and health education about its impact on life. Besides this early prevention can be done with role play in adolescents so that adolescents can analyze how LGBT prevention is. This community service was held on Saturday, November 27, 2018 with a total of 76 participants. Counseling was conducted at SMAN 9 Padang in class XI. The method used in this activity was counseling and health education with the lecture method, role play involving students and also effective teachers in schools by providing booklets and leaflets which were one of the means to increase the knowledge of teachers and students about LGBT. The existence of booklets and information leaflets will be conveyed systematically.